A Analisis Pengelolaan Limbah Padat Medis Rawat Inap Di Rumah Sakit Umum Astrini Wonogiri: Analisis Pengelolaan Limbah Padat Medis Rawat Inap di Rumah Sakit Umum Astrini Wonogiri - Devita Rahayu Nurhaliza Putri; Nurbaya, Fiqi (Jurnal Ilmu Kesehatan Masyarakat Berkala (JIKeMB), 2025)
Background: Medical solid waste management is a crucial aspect of maintaining environmental health and ensuring the safety of hospital staff and patients. Astrini General Hospital, Wonogiri, generates solid medical waste from various services, especially in inpatient care units. This study aims to analyze the medical solid waste management system, including aspects of human resources, management policies, facilities and infrastructure, segregation, storage, transportation, and final output. Method: This research employed a descriptive qualitative method using in-depth interviews, direct observations, and documentation. The study involved seven informants consisting of sanitarians, ward heads, and cleaning service staff. Data were analyzed using the Miles and Huberman interactive model. Resulth: The findings showed that most of the waste management practices were in accordance with established procedures. However, several issues remain, such as limited transport routes, suboptimal temporary storage locations, and inadequate staff training. The total volume of solid medical waste from inpatient services in one collection reached 350 kg, consisting of infectious waste, sharp objects, and pharmaceutical waste. Conclusion, Astrini General Hospital has implemented solid medical waste management fairly well. Nevertheless, improvements are needed in monitoring, infrastructure, human resources, and transportation systems. Regular training, policy evaluation, and infrastructure upgrades are recommended. Keywords: Hospital, Medical solid waste, Segregation, Transportation, Waste management